PENGARUH SIKAP MANDIRI TERHADAP MINAT BERWIRAUSAHA PESERTA DIDIK KELAS XII IPS SMA NEGERI 1 PONTIANAK - Yolanda, Diaz Erika; Basri, Muhammad; Kuswanti, Heni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research is to find out: 1) what is the independent attitude of XII IPS class students at SMA Negeri 1 Pontianak, 2) what is the interest in entrepreneurship for XII IPS class students at SMA Negeri 1 Pontianak, and three) How big is the influence on whether independence is in the hobby of entrepreneurship for XII IPS class students SMA USA 1 Pontianak. The technique used is a quantitative approach with associative methods. Took 108 students whose entire population was sampled. The statistical evaluation used is simple linear regression analysis. The test results confirmed that: 1) the impartial independent attitude of class XII IPS students at SMA Negeri 1 Pontianak became protected in the high class with a percentage of 75.214%. 2) The hobby for entrepreneurship for class XII IPS students at SMA Negeri 1 Pontianak is relatively high with a percentage of 77.42%. three) impartial independent attitude has an impact on the interest in entrepreneurship. The influence of an impartial mindset on the hobby of entrepreneurship in class XII IPS students at SMA Negeri 1 Pontianak is 58.9%. based on the results of SPSS 26 calculations, a very large fee is obtained, namely 0.000 0.05, meaning that H0 is rejected and Ha is standard. So it can be concluded that there is an influence between the attitude of bias on the interest in entrepreneurship in Class XII IPS Elegance SMA Negeri 1 Pontianak.